Water in Kentucky - Krieger, Robert A. (Robert Albert), 1918-2006.; Thomas, N. O.; Cushman, R. V. (Robert Vittum), 1916-2001; Geological Survey (U.S.); Project Muse. ([Lexington, 1969)
Lakes, rivers, and springs have shaped and nourished life in Kentucky for centuries, and water has played a pivotal role in determining Kentucky's physical, cultural, and economic landscapes. In this generously illustrated work, experts from a variety of fields explain how water has defined regions across the state.
Front Cover; TItle Page; Copyright Page; Sponsors; Contents; Introduction; Chapter One; Chapter Two; Chapter Three; Chapter Four; Chapter Five; Chapter Six; Chapter Seven; Chapter Eight; Chapter Nine; Chapter Ten; Chapter Eleven; Chapter Twelve; Chapter Thirteen; Chapter Fourteen; Chapter Fifteen; Chapter Sixteen; Chapter Seventeen; Chapter Eighteen; Chapter Nineteen; Chapter Twenty; Chapter Twenty-one; Chapter Twenty-two; Chapter Twenty-three; Contributors; Index
"Prepared by the U.S. Geological Survey in cooperation with the Kentucky Geological Survey."
Bibliography: p. 47-51.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Water-supply -- Kentucky; Eau -- Approvisionnement -- Kentucky; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Water-supply; Kentucky